1991
DOI: 10.1017/s095026880004838x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid inter-strain comparison by pyrolysis mass spectrometry of coagulase-negative staphylococci from persistent CAPD peritonitis

Abstract: SUMMARYPyrolysis mass spectrometry (PyMS) was used as a method of rapid inter-strain comparison of 19 isolates of coagulase-negative staphylococci from episodes of CAPD peritonitis. Thirteen isolates were from multiple, but distinct, episodes of peritonitis in 6 patients and the remaining 6 isolates were from 6 patients with single episodes. The results, expressed in terms of identity/non-identity of strains, were compared with those obtained using an established typing system comprising an extended antibiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…PyMS is a quick and reliable method of inter-strain comparison for many species, including streptococci [11], salmonellae [7] and staphylococci [8] and now, L. pneumophila, although the method does not yet offer formal type designations. To our knowledge this is the first occasion that PyMS has been used to trace an environmental source of clinical disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PyMS is a quick and reliable method of inter-strain comparison for many species, including streptococci [11], salmonellae [7] and staphylococci [8] and now, L. pneumophila, although the method does not yet offer formal type designations. To our knowledge this is the first occasion that PyMS has been used to trace an environmental source of clinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…The 30 mass ion peaks showing the greatest discrimination between groups were subjected to principal component (PC) and canonical variate (CV) analyses, as in previous reports [7,8] ordination diagram (combined PCCV1 v. PCCV2) if their triplicate points did not overlap any from strains within the cluster. On sequential analyses these outliers were edited out of each data set until ordination diagrams showed that few, if any, triplicates overlapped.…”
Section: Pyms Data Analysismentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Rapid methods for sub-typing analysis are crucial in clinical contexts, particularly to distinguish strains with respect to antibiotic resistance, acid resistance, toxin production capability, and other qualities that confer pathogenic character. During the last third of the past century, analytical chemists have periodically visited or revisited the potential use of mass spectrometric methods for rapid characterization of microbiological samples.…”
mentioning
confidence: 99%